The public school in the light of democratic management: the construction of protagonist training - Sulamita Bernardo de Albuquerque; Jayme Benvenuto Lima Junior (Universidade Estadual de Alagoas, 2023)
The construction of citizenship does not represent only a human aspiration, but a struggle for a dignified existence and for the opportunity to fight the deep inequalities that weaken society. Education has an important role in the formation of principles and values through the practices arising from school daily life, once the school adopts this perspective prioritizing democratic and participatory management, these aspects contemplated in the school project may represent an important tool for the construction of citizenship and youth protagonism in the school environment. Therefore, the present work aims to analyze the construction of citizenship having as a conception the implantation of democratic management and youth protagonism in the school environment. The research corpus was worked with studies on the construction of the democratic school, as theoretical reference we have Freire (1987; 1996; 2015); Gadotti (1992); Benevides (1996; 2016), from a methodological point of view, the study takes a qualitative, bibliographic and documentary approach. The results of the study indicate that the guidelines that guide schools and are responsible for providing an education based on the formation of citizenship face challenges and advances, and that the model must be constantly revised, in order to meet the objectives of an education for citizen formation.